Improving Students' Learning Outcomes on Qurba Material in Grade V Using The Discovery Learning Model at MIS Darul Azhar - Mukran; Muji Priyati (MANDAILING GLOBAL EDUKASIA, 2025)
The research was motivated by the fact that student learning outcomes in the Fiqh subject of class V at MIS Darul Azhar are still low. This is indicated by student learning outcomes below the KKM. The discovery model can be an alternative to improve student learning outcomes. Therefore, researchers are interested in conducting further research on the discovery learning model in improving student learning outcomes. The purpose of this study was to determine whether or not the application of the discovery model can improve student learning outcomes in the Fiqh subject. The type of research used in this study is classroom action research. The subjects in this study were class V students at MIS Darul Azhar, Tanah Bumbu Regency. The data collection techniques used were observation sheets, tests, and documentation. Based on the results of the study, it can be seen that the application of the discovery model can improve the learning outcomes of class V students of MIS Darul Azhar in the Fiqh subject from before the Pre-cycle Action, cycle I, and cycle II. before the action, it was known that 16 people did not complete and 12 people completed. with classical completeness of 43%, in cycle I it is known that 10 people did not complete and 18 people completed with classical completeness of 64%, and in cycle II it is known that 2 people did not complete and 26 people completed with classical completeness of 93%. Thus it can be concluded that the application of the discovery learning model can improve the learning outcomes of class V MIS Darul Azhar students in the subject of Fiqh.